Penguasaan Konsep IPA Ditinjau dari Konsep Diri dan Minat Belajar Siswa - Lin Suciani Astuti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2017)
The purpose of this study to determine the effect of self-concept and interest in learning the mastery of science concepts. The instrument used in this study is a questionnaire self-concept and interest in learning while measuring mastery of concepts based on the test of IPA. Analysis of the test data used is Multiple Regression. Results of analysis of research data to prove that: (1) there is significant influence self-concept and interest in learning together toward mastery of science concepts, this is evidenced by the value of F = 10.803> Ftabel and the Sig = 0.000 <0.05; (2) there is a significant influence on the concept of self-mastery of the concept of science, it is shown from the results of calculations which show the value t = 3,471 and sig = 0,001, lower than 0.05. (3) Interest in learning gives positive and significant impact on the mastery of science concepts. This is shown from the results of calculations which show the value t = 2.620 and sig = 0,010, lower than 0.05. Although when compared to the self-concept, interest in learning the value of sig is larger. So the concept of self is a major influence on the mastery of science concepts of the interest in learning.